Modelling the Current Response and Sensitivity of Oxidase Enzyme Electrodes, Monitored Amperometrically by the Consumption of Oxygen - Pandy Pirabaharan; M. Chitra Devi; Rajagopal Swaminathan; Lakshmanan Rajendran; Michael E. G. Lyons (Electrochem, 2022)
Biosensor behaviour is characterised by non-linear differential equations that describe well-defined physical, chemical, and biological processes. Mathematical modelling of these biosensors is highly desirable since they have many applications. These models enable the prediction of a variety of their properties. In this study, the cyclic conversion of the substrate in an amperometric biosensor with an oxidase enzyme membrane electrode is studied using a mathematical model. The governing parameters for the Michaelis–Menten kinetics of enzymatic reactions are the enzyme kinetic and diffusion rates across the enzymatic layer. In this paper, we solved the non-linear equations analytically and numerically for all experimental values of parameters. This problem is simulated in MATLAB® v2016b software using the PDE solver. Our analytical solutions are compared to simulation results to validate the proposed model.